IFPRI's strategy toward food and nutrition security: Food policy research, capacity strengthening, and policy communications - International Food Policy Research Institute (International Food Policy Research Institute, 2007)
This document sets out the strategy for the International Food Policy Research Institute (IFPRI) for the next decade. The Institute's vision and mission are cornerstones of the strategy: IFPRI's Vision is a world free of hunger and malnutrition, and IFPRI's Mission is to provide policy solutions that reduce poverty and end hunger and malnutrition. The strategy addresses issues relevant to its vision and mission, including: poverty, hunger, and malnutrition in the developing world, which remain persistently high; a rapidly changing policy environment, which makes the decisionmaking process more complex and diffuse, involving many more actors at global and subnational levels and within the private and civil sectors, as well as the public sector; new technologies, which offer great promise for advancing food and nutrition security and for which research is needed to identify policies and institutions to ensure that poor people benefit from these technologies; and global health issues, which pose significant threats to food security and nutrition."